Desain Pemilu Ideal: Kedekatan Optimal dengan Implikasi Coattail effect - Fyna Rahmatika Elba; Enika Maya Oktavia; Dimas Nur Akbar Palatal; Pinto Kaganti Afwan Halim (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
General elections are pivotal moments in the dynamics of a country's democracy, including in Indonesia. Elections involve various political parties coalitioning to nominate their leaders. This study compares the coattail effect's impact on the 2019 and 2024 elections. The research method employs a normative approach with comparative, conceptual, and historical analyses. Secondary data were collected from various sources. The results indicate differences in the coattail effect's impact between the two elections. Although the popularity of presidential candidates can influence the vote share of their supporting political parties, the effects are not always consistent. In the 2024 election, Prabowo-Gibran won the majority vote, but the coattail effect only occurred for their main supporting party. Conversely, in the 2019 election, PDIP and PKB experienced a more significant coattail effect. The analysis also suggests that the ideal electoral design with a coattail effect involves changing the electoral system to a closed proportional system and removing the Presidential threshold. This study is crucial for understanding the political dynamics within Indonesia's democratic system.